Log in to add a comment

## Answers

*We cant derive that 0!=1*

*But we can see that 0!=*

*Which equals to 1*### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

To Prove:- 0! =1.

Known:y! = y x (y-1)!

So, 1! = 1 x (1-1)!1! = 0!

or

0! = 1! -(a)

Proof:As We know,n! = n x n-1 x n-2 x n-3 x n-4 x .......... 2 x 1

So,4! = (3+1)!

= 4 x 3!

= 4 x 3 x 2 x 13!

= (2+1)!

= 3 x 2!

= 3 x 2 x 1 2!

= (1+1)!

= 2 x 1!

= 2 x 11!

= (0+1)!

= 1 x 0! = 1 -(b)

Hence, from (a) and (b)We get, 0! = 1

Known:y! = y x (y-1)!

So, 1! = 1 x (1-1)!1! = 0!

or

0! = 1! -(a)

Proof:As We know,n! = n x n-1 x n-2 x n-3 x n-4 x .......... 2 x 1

So,4! = (3+1)!

= 4 x 3!

= 4 x 3 x 2 x 13!

= (2+1)!

= 3 x 2!

= 3 x 2 x 1 2!

= (1+1)!

= 2 x 1!

= 2 x 11!

= (0+1)!

= 1 x 0! = 1 -(b)

Hence, from (a) and (b)We get, 0! = 1